New management of social services - international perspectives - Bornarova, Suzana (Ревија за социјална политика/Journal of Social Policy, 2019)
Social service systems have undergone considerable development in the last several decades internationally. This development has been driven by the unprecedented demographic changes related to population aging, dropping fertility rates, as well as by the changes in family structures and weakening of the informal care capacities of families. These circumstances have entailed an increase in the population needs for different social services and required a corresponding response by the welfare states to respond to those needs. This article aims to provide a brief overview of this state response. Namely, it will focus on the key trends at international and European level applied by welfare states regarding management of social service systems, such as: residualism, marketization, decentralization, integrated service delivery and deinstitutionalization.